1990
DOI: 10.1111/j.2042-7158.1990.tb14379.x
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison Between Nonionic Micelles and Microemulsions As A Means of Incorporating the Poorly Water Soluble Drug Diazepam

Abstract: The ease of preparation, thermodynamic stability, optical transparency and ability to sterilise by filtration renders microemulsion systems an attractive prospect for use in d r q delivery. In this investigation we attempt to determine whether these systems offer advantages over micellar preparations in the formulation of poorly water soluble drugs.We compare the incorporation of a model poorly water soluble drug, diazepam (log P =2.6), in both micellar solutions of polyoxyethylene-10-oleyl ether (Brij 96), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…The penetration enhancer effect of the excipients of the microemulsion has been reported (9). Lastly, the high drug loading capacity of microemulsions allows the administration of higher concentrations of poorly soluble drugs (14,15). These physicochemical phenomena are particularly prominent in the case of bicontinuous microemulsions regarded as dispersions with very low interfacial tension, highly fluctuating interface and higher solubilising properties compared to globular microemulsions (16,17).…”
Section: Introductionmentioning
confidence: 94%
“…The penetration enhancer effect of the excipients of the microemulsion has been reported (9). Lastly, the high drug loading capacity of microemulsions allows the administration of higher concentrations of poorly soluble drugs (14,15). These physicochemical phenomena are particularly prominent in the case of bicontinuous microemulsions regarded as dispersions with very low interfacial tension, highly fluctuating interface and higher solubilising properties compared to globular microemulsions (16,17).…”
Section: Introductionmentioning
confidence: 94%
“…Research indicated that the unique structural organization of the phases in microemulsion contribute to additional solubility regions, increasing the load capacity of the microemulsion, compared to non-structured solutions containing the same fraction of the constituents, which principally can form microemulsion. [30][31][32][33] Microemulsions are having a capability of incorporating a large variety of lipophilic and hydrophilic phases. The increased solubility of the drug in the microemulsion is by the virtue of the increase in the additional solubilization sites of the lipophilic and hydrophilic moiety of the surfactant interface film formed in the microemulsion.…”
Section: Solubilising Property Of Microemulsionsmentioning
confidence: 99%
“…Nonionic and zwitter ion -based surfactants (such as certain phospholipids) offer a more pharmaceutically acceptable alternative. Several research groups have been focusing on formulating ME systems using a single surfactant such as lecithin [98,111,112] or n -alkyl POE (polyoxyethylene ethers) [14,112,113] . This approach tends to compromise the phase behavior of ME -forming systems.…”
Section: Transdermal Drug Deliverymentioning
confidence: 99%